SOSIALISASI TERAPI HAND HELD FAN (KIPAS ANGIN GENGGAM) UNTUK MENGATASI PERNAPASAN PADA PASIEN GAGAL JANTUNG DI RUANG CARDIOVASCULAR CARE UNIT (CVCU) RSUD KARAWANG - Yumi Dian Lestari; Grace Evelyn; Sri Nuriyah (Bajang Institute, 2024)
Heart failure is a chronic cardiovascular problem that often causes shortness of breath (dyspnea), especially during light activity or while lying down. Shortness of breath can reduce comfort and quality of life, and worsen the patient's psychological condition. One effective, safe, and easy-to-do non-pharmacological intervention to reduce shortness of breath is the use of a handheld fan. The airflow from the fan is directed to the face and nose area, which can stimulate trigeminal receptors, thereby increasing the sensation of relief when breathing. This community service activity aims to improve the knowledge and skills of nurses in implementing handheld fan therapy as a non-pharmacological measure to overcome shortness of breath in heart failure patients. The activity was carried out through socialization, demonstrations, and direct practical training in the CVCU Room of Karawang Regional Hospital. Participants consisted of 20 cardiac nurses and 5 nursing students. Evaluation was carried out through a pre-posttest of knowledge, as well as observations of satisfaction and practical skills. The results of the activity showed an average increase in participants' knowledge from 60% to 95%, and practical skills from 50% to 90%. Participants stated that this therapy was very easy to perform, did not require special medical equipment, and provided a relief and comfort effect for patients. Socialization of hand-held fan therapy effectively improves nurses' knowledge and skills in providing non-pharmacological interventions for heart failure patients with shortness of breath. This therapy can be used as an alternative to support nursing interventions to improve patient comfort.